International Conference on Simulation of Semiconductor Processes and Devices, 2003. SISPAD 2003. 2003
DOI: 10.1109/sispad.2003.1233702
|View full text |Cite
|
Sign up to set email alerts
|

Substrate resistance extraction using a multi-domain surface integral formulation

Abstract: In recent years, mixed-signal designs have become more pervasive, due to their efficient use of area and power. Unfortunately, with sensitive analog and fast digital circuits sharing a common, non-ideal substrate, such designs carry the additional design burden of electromagnetic coupling between contacts.This thesis presents a method that quickly extracts the electroquasistatic coupling resistances between contacts on a planar, rectangular, two-layer lossy substrate, using an FFT-accelerated multi-domain surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…If the electrical conductivity σ e is constant, in 2-D form, substituting (2) and (3) into (1) yields…”
Section: ) DC Electric Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…If the electrical conductivity σ e is constant, in 2-D form, substituting (2) and (3) into (1) yields…”
Section: ) DC Electric Fieldmentioning
confidence: 99%
“…Horowitz et al [1] have presented a new algorithm for extracting the resistance from an integrated circuit artwork and shown that accurate resistance values can be determined by using a heuristic approach with 2-D current flow. Vithayathil et al [2] developed an iterative method that can simulate large substrate coupling problems with a large number of unknowns accurately. A 3-D direct BEM (DBEM) was utilized that produced highly accurate results on a typical 52-contact substrate structure as shown in [3].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance calculation is a fundamental component of any standard VLSI layout extraction flow. Several algorithms have been proposed for resistance calculation, ranging from simple analytical formulae to complex field solvers [1,2,3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%